Dazbogosoma mokoshae, a new cavernicolous species of the previously monospecific genus Dazbogosoma Makarov & Ćurčić, 2012, from Serbia (Diplopoda: Chordeumatida: Anthroleucosomatidae) - Šević, Mirko; Antić, Dragan; Stojanović, Dalibor; Makarov, Slobodan (Zootaxa, 2022)
A new troglobiotic species, Dazbogosoma mokoshae sp. nov., is described from a cave in the eastern Serbia. This is the second species from the previously monospecific genus Dazbogosoma Makarov & Ćurčić, 2012. An updated diagnosis of the genus, as well as a diagnosis, detailed description, illustrations and in situ photographs of a new species, based on both males and females, are presented. The distribution and relationships within the “Bulgarosoma” complex comprising D. mokoshae sp. nov. are briefly discussed.